1993
DOI: 10.1084/jem.177.6.1809
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human interferon-inducible protein 10 is a chemoattractant for human monocytes and T lymphocytes and promotes T cell adhesion to endothelial cells.

Abstract: SummaryThe human cytokine interferon-inducible protein 10 (IP-10) is a small glycoprotein secreted by activated T cells, monocytes, endothelial cells, and keratinocytes, and is structurally related to a family of chemotactic cytokines called chemokines. Although this protein is present in sites of delayed-type hypersensitivity reactions and lepromatous leprosy lesions, the biological activity of IP-10 remains unknown. We report here that recombinant human IP-10 stimulated significant in vitro chemotaxis of hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
423
2
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 696 publications
(445 citation statements)
references
References 23 publications
18
423
2
2
Order By: Relevance
“…The CXCL10/CXCR3 axis plays a critical role in inflammation by recruiting activated T lymphocytes, monocytes, and macrophages. 12,14,58,60 We found that CXCL10 expression is up-regulated in cells, including RGCs, after axonal injury, which is associated with leukocyte recruitment and infiltration in neural retina. To investigate potential mechanisms of CXCR3-mediated RGC death in TON, we deleted CXCR3 in leukocytes and found that leukocyte recruitment is attenuated and RGC survival is increased.…”
Section: Discussionmentioning
confidence: 78%
“…The CXCL10/CXCR3 axis plays a critical role in inflammation by recruiting activated T lymphocytes, monocytes, and macrophages. 12,14,58,60 We found that CXCL10 expression is up-regulated in cells, including RGCs, after axonal injury, which is associated with leukocyte recruitment and infiltration in neural retina. To investigate potential mechanisms of CXCR3-mediated RGC death in TON, we deleted CXCR3 in leukocytes and found that leukocyte recruitment is attenuated and RGC survival is increased.…”
Section: Discussionmentioning
confidence: 78%
“…Of all the cytokine genes that are known to be induced in vivo by DMXAA in murine tissues (Cao et al, 2001), only mRNA for IP-10 was up-regulated in cultures of HECPP cells (Figure 2A). IP-10 is known for its chemotactic (Luster et al, 1985;Taub et al, 1993) and anti-angiogenic activities (Angiolillo et al, 1995) but has no reported apoptotic activity. Our results here suggest that DMXAA may have a direct apoptotic effect on endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of ligand to CXCR3 is crucial for chemotaxis of these receptor positive cells to inflammatory sites (5). CXCL10 is regarded as a chemoattractant preferentially for activated T-cells (6) and particularly Th1 cells (7).…”
Section: Macrophages Dendritic Cells and Natural Killer T-cells) Andmentioning
confidence: 99%